(untitled) (Singapore, 1982)
This book contains selected saying from the Analects but, unlike the original which is loosely gatherred into "books", the saying are classified under five themes to make it easier for the reader to understand the ideas of Confucius. The themes are: self-cultivation, education, politics and economics, rites and music, and religion.
Keywords: Confucius,Nho giáo